Analisis SWOT Strategi Pemasaran Kredit Serta Usulan Program Kerja dengan Menggunakan Metode Analytical Hierarchy - Sony Kuswandi; Candra Moch. Surya (LPPM Institut Nasional Laa Roiba Bogor, 2021)
Rapid changes that occur in the business environment require that every business actor need to pay attention and respond to their environment, then formulates strategies in order to be able to anticipate changes in the achievement of company goals. PT. Bank BTN Purwakarta branch must be able to determine the right strategy so that the company can maintain its existence in the world of banking. Based on the results of the SWOT analysis, the company strategy needs to be developed in order to maintain strong business competitiveness. Creating a work procedure or better known by the name SOP (Standard Operating Procedure) or in Indonesia language called as TTP (Tata cara Tetap Pelaksanaan) become very important, working procedure is a reference on how we do our jon in the company.